IL-10 and regulatory T cells cooperate in allergen-specific immunotherapy to ameliorate allergic asthma - Bohm, Livia; Maxeiner, Joachim; Meyer-Martin, Helen; Reuter, Sebastian; Finotto, Susetta; Klein, Matthias; Schild, Hansjorg; Schmitt, Edgar; Bopp, Tobias; Taube, Christian (Journal of Immunology, 2015)
Human studies demonstrated that allergen-specific immunotherapy (IT) represents an effective treatment for allergic diseases. IT involves repeated administration of the sensitizing allergen, indicating a crucial contribution of T cells to its medicinal benefit. However, the underlying mechanisms of IT, especially in a chronic disease, are far from being definitive. In the current study, we sought to elucidate the suppressive mechanisms of IT in a mouse model of chronic allergic asthma. OVA-sensitized mice were challenged with OVA or PBS for 4 wk. After development of chronic airway inflammation, mice received OVA-specific IT or placebo alternately to airway challenge for 3 wk. To analyze the T cell-mediated mechanisms underlying IT in vivo, we elaborated the role of T-bet-expressing Th1 cells, T cell-derived IL-10, and Ag-specific thymic as well as peripherally induced Foxp3(+) regulatory T (Treg) cells. IT ameliorated airway hyperresponsiveness and airway inflammation in a chronic asthma model. Of note, IT even resulted in a regression of structural changes in the airways following chronic inhaled allergen exposure. Concomitantly, IT induced Th1 cells, Foxp3(+), and IL-10-producing Treg cells. Detailed analyses revealed that thymic Treg cells crucially contribute to the effectiveness of IT by promoting IL-10 production in Foxp3-negative T cells. Together with the peripherally induced Ag-specific Foxp3(+) Treg cells, thymic Foxp3(+) Treg cells orchestrate the curative mechanisms of IT. Taken together, we demonstrate that IT is effective in a chronic allergic disease and dependent on IL-10 and thymic as well as peripherally induced Ag-specific Treg cells.
EVALuna2:25968